Electroporation of lignocellulosic biomass - Aaron, Kong Chak Ho (2019)
Electroporation (EP) is versatility, rapid and high efficiency pretreatment technique using high voltage toward biomass feedstock. It is effectively and applicability to nearly all cell and species types. At the same time, Lignocellulosic biomass (Pistia Stratiotes) is the most abundant renewable bioresources on earth. The cellulose and hemicellulose contained in lignocellulosic biomass can be suitable substrate for bioethanol production. However, electroporation pretreatment technique still not widely use in this world. Therefore, this project was designing and fabricating an electric circuit and reactor to conduct electroporation treatment on lignocellulosic biomass (Pistia) in order to promote electroporation pretreatment technique. The performance of the circuit over the cell structure changes of the pistia will then test by doing electroporation treatment. In this project, Bluetooth HC-05 module was use as a region to communicate mobile phone with Arduino to control pulse width modulation (PWM) to produce high voltage square wave pulse. The high output voltage was produced by a DC step-up pulse generator which draw input source from 6V battery and controlled by SPDT relay for switching ON/OFF purpose. To prioritize the safety of user, LCD, buzzer and LEDs added to give signal and warning to user when the electric circuit is working. Bluetooth also one of the safety feature because user can control circuit by mobile phone and do not have to contact with the circuit to reduce the chance for getting shock. The reactor contains the container and electrodes with use to put the biomass sample and conduct treatment. Acrylic is chosen as the material to fabricate the container due to its transparency, electric and thermal insulated. Aluminum sheet was cut into small size to use as electrodes because it has high conductivity, not easy to get rust and low cost. Electroporation treatment is carried out to validate the electric circuit and reactor. The leaves of pistia stratiotes was dry in oven and then mashed into small particle to mix in water for treatment purpose. Sample was collected before treatment and during treatment from the mixture and then the sample cell structure analyzed under scale electron microscope (SEM). As a result, very obvious crack can be observed on the sample cell structure that undergo electroporation treatment compare to the sample cell before treatment. From the result, the cell structure of pistia was successfully disrupted, cellulose and hemicellulose can be extracted from it.